Development of wireless device for elderly care monitoring - VIJAYAKUMARAN, SATHYA (2018)
Demands for elderly care monitoring is constantly rising along with the ageing population. The numbers of falls experienced by elderly and number of elderly getting lost due to dementia is extremely worrying. With proper monitoring, these numbers could reduce significantly. This report shows the development of a wearable device with fall detection and GPS location tracking capability which is targeted at reducing the number of such incidents. Sensors which are suitable for achieving such capabilities have been identified and evaluated. Also, the report identifies the most efficient method of sending notification to caregivers and presents the implementation of push notification in an IoT platform. In this project, a detailed description of design parameters, technical specification, and programming algorithms have been provided. Also, an evaluation of the device and future recommendations have been discussed.